Exploration of Premium Factors for Passenger Vessel in Indonesia - Sridhani Lestari Pamungkas; Raja Oloan Saut Gurning; Dhimas Widhi Handani (International Journal of Marine Engineering Innovation and Research, 2025)
The premium of Indonesian marine insurance is one of the issues for maritime players in Indonesia, particularly for passenger vessels. Indonesian government also released some policies as a part of positive initiatives to bring Indonesia to the next level of maritime involvement in the world, however, the insurance side as the main risk protection of maritime operation is not positioned as the main part to be discussed. Marine insurance is the key to managing the overall risk of the passenger vessels during the operation. In fact, in Indonesia, insurance studies still have a gap in their application, particularly for the marine insurance industry and for passenger vessel insurance. The underwriter has difficulties in assessing the real risk of Indonesian passenger vessels while the shipowners do not put safety as their top priority in managing the business. This research aims to solve two main problems in Indonesian passenger vessel insurance; the first one is to identify the problems of Indonesian passenger vessel insurance and the second is to explore and identify the premium factors of Indonesian passenger vessel insurance. The study found that the big claim ratio reported over the years, the lack of marine insurance underwriters’ ability to assess the risk, the lack of marine insurance capacity, and the premium war are the main problems faced by Indonesian passenger vessel insurance players. Accordingly, this paper is also revealing several premium factors for Indonesian passenger vessel insurance; including the vessel type, GT, claim record, years of built, trading area, extent of insurance coverage, vessel condition, as well as the moral hazard from the owner and the crew.